The Effects of Healthy Aging on Right Ventricular Structure and Biomechanical Properties: A Pilot Study - Sharifi Kia, Danial; Shen, Yuanjun; Bachman, Timothy N.; Goncharova, Elena A.; Kim, Kang; Simon, Marc A. (Frontiers in Medicine, 2022)
Healthy aging has been associated with alterations in pulmonary vascular and right ventricular (RV) hemodynamics, potentially leading to RV remodeling. Despite the current evidence suggesting an association between aging and alterations in RV function and higher prevalence of pulmonary hypertension in the elderly, limited data exist on age-related differences in RV structure and biomechanics. In this work, we report our preliminary findings on the effects of healthy aging on RV structure, function, and biomechanical properties. Hemodynamic measurements, biaxial mechanical testing, constitutive modeling, and quantitative transmural histological analysis were employed to study two groups of male Sprague-Dawley rats: control (11 weeks) and aging (80 weeks). Aging was associated with increases in RV peak pressures (+17%, p=0.017), RV contractility (+52%, p= 0.004), and RV wall thickness (+38%, p=0.001). Longitudinal realignment of RV collagen (16.4°, p=0.013) and myofibers (14.6°, p=0.017) were observed with aging, accompanied by transmural cardiomyocyte loss and fibrosis. Aging led to increased RV myofiber stiffness (+141%, p=0.003), in addition to a bimodal alteration in the biaxial biomechanical properties of the RV free wall, resulting in increased tissue-level stiffness in the low-strain region, while progressing into decreased stiffness at higher strains. Our results demonstrate that healthy aging may modulate RV remodeling via increased peak pressures, cardiomyocyte loss, fibrosis, fiber reorientation, and altered mechanical properties in male Sprague-Dawley rats. Similarities were observed between aging-induced remodeling patterns and those of RV remodeling in pressure overload. These findings may help our understanding of age-related changes in the cardiovascular fitness and response to disease.